Human leptospirosis cases in Palermo Italy. The role of rodents and climate. Issue 2 (March 2018) - Vitale, Maria; Agnello, Stefano; Chetta, Michele; Amato, Benedetta; Vitale, Giustina; Bella, Calogero D.; Vicari, Domenico; Presti, Vincenzo D.M.L.
Abstract: Many regions of the world are increasingly exposed to leptospirosis due to poverty, global warming and high urban density. Here, we report a molecular survey for pathogenic Leptospira spp. in rodents and two symptomatic human cases of leptospirosis in the city of Palermo, Italy. Four rodent species were captured in six areas of the city, and a molecular analysis for pathogenic Leptospira spp. on DNA from the kidney samples showed a different prevalence of leptospirosis in all the species of rodents. In addition, two human cases that occurred in May and October of 2009 in the city were also reported. A 67-year-old woman recovered after antibiotic treatment, whereas a 71-year-old woman did not survive. The weather during both of those times was notable for a violent cloudburst that caused street flooding. For the past several years, the incidence of leptospirosis has remained steady at 9 human cases every 10 years across the entire island of Sicily, with a population of almost 5 million inhabitants. The high prevalence of leptospirosis in rodents and the simultaneous presence of known risk factors, such as a mild/wet climate, street flooding and garbage accumulation, could explain the two cases of leptospirosis within the same city in the same year. This occurrence should raise awareness of this under-estimated zoonosis among public health authorities, especially given the potential fatality among elderly and immune-compromised individuals in urban settings in developed countries.